How to Handle a Case of Redundant Publications in Four Elsevier Journals? - Jaime A. Teixeira da Silva (CV. Literasi Indonesia, 2023)
Current ethical guidelines, as defined by the Committee on Publication Ethics (COPE), note that redundant publications or duplicate copies should be retracted because they partake no new information, and may be perceived as unfair. Elsevier and its journals are COPE members. In 2000, four Elsevier journals (Anaerobe, Journal of Theoretical Biology, Journal of Autoimmunity, Food Microbiology) published an identically worded notice related to the digital object identifier (DOI), i.e., it was published in quadruplicate (four copies). Despite an alert to all four journals about this quadruplicate, none were retracted. If academics would like to cite this announcement, which of the four copies should they use? This case study raises an important deontological argument regarding the laissez-faire attitude of these journals, which charge a fee (US27.95-31.50) to access this document’s four PDFs. Yet, other cases of duplications/redundant publication in Elsevier journals are frequently retracted. In the case of these four DOI-related papers, what does ignoring the three redundant copies suggest?